Effect of Dry-Air Chilling on Warner-Bratzler Shear Force and Water-Holding Capacity of Broiler Breast Meat Deboned Four Hours Postmortem - Zhuang, H.; Savage, E.M.; Smith, D.P.; Berrang, M.E. (International Journal of Poultry Science, 2008)
Advantages of air chilling (AC) methods over immersion chilling (IC) methods in quality retention and improvement of deboned chicken breast meat depend on experimental conditions, such as deboning time. The objective of this study was to evaluate the effect of a dry-AC method on shear force and water-holding capacity (WHC) of broiler breast meat deboned 4h postmortem compared to hot-boned (no chill) or immersion-chilled meat. Ready-to-cook broiler carcasses were hot-boned, chilled by ice water immersion (0.3 °C, 50 min) or chilled by cross-flow cold, dry air (0.7 °C, 150 min). Pectoralis (p.) major and p. minor were removed from the bone at 4 h postmortem. Shear force was measured using a Warner-Bratzler (WB) method and WHC was estimated using cooking yield, drip loss, amount of bound water (filter paper method) and water uptake (swell/centrifugation method). Regardless of muscle type, the WB shear force value of AC samples was significantly lower than that of hot-boned samples; however, there was no difference in the shear force between AC and IC. Regardless of measurement methods, there were no differences (P > 0.05) in WHC between the three treatments. These results demonstrate that when compared to no chill, AC followed by 4 h postmortem deboning can lead to a difference in WB shear values while WHC properties can be retained. For broiler breast meat deboned 4 h postmortem, AC does not result in any significant differences in shear force and WHC when compared to IC.